SYSTEM DESIGN COOPERATION ON BORROWING MONEY FROM EMPLOYEES RI ACCOUNTING HIGH SCHOOL STATE (KPRI-STAN) USING MICROSOFT VISUAL BASIC 6.0 - Restiani Restiani; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2005)
The use of computer technology at the present time is very much needed in data management both in the number of large and small. Because in addition can also save time and effort to minimize errors that occur if done manually. Here in the money lending system run by Servants Cooperative State Accountancy College of RI are still using manual system. So the writer will give the proposal that there be a manual system to computerized system, to process data or information become more effective and efficient.In scientific writing, the design of the Money Lending System of RI Employees Cooperative State Accounting College (KPRI-STAN) is created by using Visual Basic 6.0 programming language and for the database using Microsoft Access. In order for data to be processed more easily, quickly, precisely and accurately.